Developing a roadmap for Health Technology Assessment implementation in public health decisions. (30th September 2020) - Di Macio, F; Caricato, M; Primieri, C; Favaretti, C; De Waure, C
Abstract: Issue: Although the recognized importance of Health Technology Assessment (HTA) in fostering health policy and management, little is known and differences emerge in the state of the art of HTA development and use in public health decisions. Description of the Problem: HTA applied to public health interventions could lead to improved population's health, risk factor reduction and high quality services. All these factors represent the basis of health care system sustainability. Nevertheless, there is a lack of evidence about the application of HTA to public health. In this light, the Section on HTA of the European Public Health Association (EUPHA) is conducting a Delphi process in order to define a shared roadmap for the implementation of HTA in public health. Results: A literature search was first performed on PubMed to identify useful documentation for drafting the roadmap. Taking clues from Kalò et al., who drafted an HTA roadmap scorecard to support HTA implementation in Central and Eastern Europe, a preliminary core set of actions and pillars to pave the way for the implementation of HTA in public health, was identified. Then, a group of HTA experts was invited to participate to the Delphi process with the aim to build consensus on the final set of actions and pillars to include in the roadmap. Lessons: Evidence on the ways to strengthen the role of HTA in public health decisions is scant and the development of a shared roadmap could be useful to identify milestones to do it. Key messages: HTA applied to public health could promote an efficient, sustainable, equitable and high-quality health system. Nevertheless, the role of HTA in taking public health decisions should be strengthened. As evidence on the application of HTA in public health is scant, the development of a shared roadmap could enhance fostering its use in taking decisions on public health interventions.